Statehood and the law of self-determination - Raič, D. (Developments in international law ;, 2002)
This text examines the modern law of statehood, and in particular the role of the law of self-determination in the process of the formation of States in international law. The study shows that the law of statehood has changed considerably since the establishment of the United Nations.